DESAIN ALAT PENUNJANG AKTIVITAS BERJALAN BAGI PASIEN BERISIKO JATUH - Hatguina; Ariani; Hendy Rosadi; Woro Asty Werdina (Jurnal Dimensi Seni Rupa dan Desain, 2023)
Every human being has different physical conditions and health. There are humans who have a rather weak physical condition, so they experience limitations in walking and other activities.  They need support on the legs as support during activities, as well as minimizing the possibility of falling, especially for patients who are at risk of falling.   This study aims to find problems in existing walking activity support tools   to further provide design alternatives as recommendations for solving problems.  A descriptive method of analysis is applied to explain the design of a walking activity support tool for patients at risk of falling. The data in this study were obtained from the results of surveys, direct observations, interviews, literature studies, and referred to theoretical foundations according to experts.  The results showed that existing products are mostly intended for the elderly with conventional designs. Therefore, design recommendations pay attention to the concept of walking activity support tools that can help the activities and movements of people who have experienced a fall (post-fall) and prevent patients who have the potential to fall. Ergonomic factors, especially in the ease of product operations, as well as a more universal design are the points that are considered in this design. These fall prevention efforts are expected to contribute to the achievement of the key Sustainable Development Goals (SDGs) of ensuring healthy lives and promoting well-being for all people at all ages (goal 3). Keywords: supporting tools, walking activities, risk of falling, patients